22. SEXUAL PROBLEMS AMONG OLDER ADULTS IN ASIA AND AFRICA: A REVIEW (Vietnam Journal of Community Medicine, 2024)
The aim of this review was to explore the prevalence of sexual problems among older adults in Asia and Africa; and to analyze how difficult it was for them to seek help. Sexual problems are characterized by diminished or absent of sexual interests and by disturbances in the physiological or psychosocial patterns associated with sexual response cycle. Male sexual dysfunction (ED) and female sexual dysfunction increase with age. Studies show that about 33% of the elderly population has at least one complaint with their sexual functioning. Old people face shame and hesitancy when consulting health-care professionals for sexual problems due to the taboos surrounding sex, compounded by a lack of knowledge of older sexuality and ageism in healthcare. The General Practitioners (GP) on the other hand, tend to ignore older adult’s complaints due to lack of training, or just perceiving sexual problems is a norm at old age. However, GP should always give their clients’ opportunity to voice out their concerns with sexual function and offer them various health care regimen and alternatives for evaluation and treatments.
Keywords: Older adults; sexual dysfunction; menopause; Africa; Asia